Shape Optimization of A Parabolic Trough Collector, Geometrical Considerations - Radia, AIT EL CADI (2022)
In the last years, solar thermal power plants based on parabolic trough concentrators (PTCs), which are the most proven type of the Concentrating Solar Power technologies (CSP), have been widely deployed in the industry sectors. Indeed, there are various applications for thermal plants in industry, such as desalination, refrigeration and air heating. The optimization of the mirror surfaces design is basic to characterize the whole solar energy conversion system. In this paper the basic geometrical parameters a typical PTC are presented and the optical performances of this collector is studied basing on these parameters.